The specificity and the difference of nursing care in preoperative and postoperative geriatric patients - Cebulska, Violetta; Koźlak, Violetta (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Surgery in geriatric patients can lead to greater exposure to complications and problems with nursing care than in younger people. The knowledge of needs and health expectations of this group of patients is the basic condition to provide professional preoperative and postoperative care. Aim of the study. The aim of this research was to obtain nurses’ opinions about the most frequently occurring problems in preoperative and postoperative nursing care in geriatric patients. Materials and methods. Fifty nurses participated in the research working on surgical, orthopaedic and neurosurgical wards of The Ludwik Perzyna Regional Hospital in Kalisz. The self-created questionare of 26 questions was used to achieve the assumed goal. Results. As far as the respondents opinions are concerned, various perioperative and postoperative problems, which require nursing intervention, occure more often in elderly patients. When planning the care for a geriatric patient, nurses use the nursing process method. The biggest problems in taking preoperative and postoperative nursing care result, among other things, from motor activity disorders of a patient and difficulties in communicating. Those polled express the need to participate in various forms of professional inservice training, in order to serve the hospitalized geriatric patient better. Conclusions. Nursing staff notices the specificity and the differences of nursing care in preoperative and postoperative geriatric patients. Nursing intervention in postoperative period to a large extent includes solving problems connected with complications in a patient’s physical condition. In postoperative nursing care the significant impediments are motor activity disorders, mental disorders and the sense organs disturbances. Increased supervision of the patient and necessity to create conditions of greater physical and mental comfort, require from the nurses to have a broad knowlegde of specific methods and techniques how to work with a patient.